2024
DOI: 10.14336/ad.2023.0519-1
|View full text |Cite
|
Sign up to set email alerts
|

Role and Potential Mechanisms of Nicotinamide Mononucleotide in Aging

Abstract: Nicotinamide adenine dinucleotide (NAD + ) has recently attracted much attention due to its role in aging and lifespan extension. NAD + directly and indirectly affects many cellular processes, including metabolic pathways, DNA repair, and immune cell activities. These mechanisms are critical for maintaining cellular homeostasis. However, the decline in NAD + levels with aging impairs tissue function, which has been associated with several age-related diseases. In fact, the aging population has been steadily in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…The most significantly upregulated metabolite in casM was the unsaturated fatty acid, PI (16:1/18:2), with log2FC of 13.14, while the most downregulated was guanosine, with a log2FC of - 6.79. CasM mice exhibited elevated levels of various metabolites associated with healthy aging, anti-skin aging, and anti-inflammation, such as ectoine [35], resolvin D2 [36], oleamide [27, 28], taurine [37], taurocholic acid [38], taurodeoxycholic acid [39], nicotinamide [40], ascorbic acid (vitamin C) [41], D- pantothenic acid (vitamin B5) [42, 43] and choline [44] ( Figure 4C ). Similar to shamF, casM mice also showed an enrichment of anti-oxidative metabolites likely derived from plant-based foods, including ganoderenic acid C [45], oleuropeic acid [46], fasciculol C [47], graveoline [48] ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…The most significantly upregulated metabolite in casM was the unsaturated fatty acid, PI (16:1/18:2), with log2FC of 13.14, while the most downregulated was guanosine, with a log2FC of - 6.79. CasM mice exhibited elevated levels of various metabolites associated with healthy aging, anti-skin aging, and anti-inflammation, such as ectoine [35], resolvin D2 [36], oleamide [27, 28], taurine [37], taurocholic acid [38], taurodeoxycholic acid [39], nicotinamide [40], ascorbic acid (vitamin C) [41], D- pantothenic acid (vitamin B5) [42, 43] and choline [44] ( Figure 4C ). Similar to shamF, casM mice also showed an enrichment of anti-oxidative metabolites likely derived from plant-based foods, including ganoderenic acid C [45], oleuropeic acid [46], fasciculol C [47], graveoline [48] ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…17 NMN is a precursor to the biosynthesis of NAD + and has received a great deal of attention in recent years for its anti-ageing properties. 18 Studies have indicated a connection between the degeneration of the colon and changes in NAD + levels in ageing mice, 19 and some other studies have shown that NMN supplementation can help protect anti-inflammatory, antioxidant, and barrier functions in the jejunum, however, further research on the role of NMN in colonic function, ISCs, microbiota, and metabolites of senescent mice is still lacking. 20 Therefore, an integrated analysis was carried out to assess the changes in the survival rates of Zmpste24 −/− mice following the oral intake of NMN.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a comprehensive understanding of NMN metabolism and dynamic regulation remains incomplete, particularly regarding NMN's cellular uptake, 9 subcellular concentrations 10,11 and intracellular transport mechanisms. 12 To address these questions, the precise measurement of NMN levels with spatial and temporal resolution is much needed. Currently, NMN quantification relies on chromatography, 13,14 mass spectrometry, 15 enzymatic assays 16,17 or chemical probes, 18 all of which require sample lysis and thus compromise the intrinsically rich spatiotemporal information of the biological processes.…”
Section: Introductionmentioning
confidence: 99%